(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Laser engraving is one of the most commonly used laser procedures for interacting with laser material. The speed, ease of use and high precision make it an attractive process for use by manufacturers and for removing insulation from various cables. Cable stripping is a particularly common operation in aeronautics. The aircraft is equipped with several hundred kilometers of cables to control and operate the various systems of the aircraft and most of these cables must be stripped at both opposite ends to allow the cable to be connected to different terminals.This report examines the possibility of removing polyvinyl chloride (PVC) insulation from telecommunication cables of different colours and thicknesses up to 600 [μm]. The experimental measurements of the study were performed with a low-power continuous CO2 laser system. The main functional dependence of the width and depth of the ablation zone on the main technological parameters, such as the average power and the processing speed, have been experimentally studied. The zones of laser impact are observed with a laser microscope. The graphic dependencies are analyzed in order to determine the optimal working intervals.The analysis aims to help solve problems related to the application of small diameter communication cables in the production of various communication devices and components for the needs of industry.